2021
DOI: 10.3389/fimmu.2021.647329
|View full text |Cite
|
Sign up to set email alerts
|

Functions for Retinoic Acid-Related Orphan Receptor Alpha (RORα) in the Activation of Macrophages During Lipopolysaccharide-Induced Septic Shock

Abstract: The transcription factor Related Orphan Receptor Alpha (RORα) plays an important role in regulating circadian rhythm, inflammation, metabolism and cellular development. Herein we show that in the absence of functional RORα in mice there is reduced susceptibility to LPS-induced endotoxic shock, with selective decreases in release of pro-inflammatory cytokines. Treatment of mice with a RORα selective synthetic inhibitor also reduced the severity of LPS-induced endotoxemia. The reduction in responses in Rora defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The RORs have different tissue expressions; RORa is present predominantly in organs, while RORy is lymphatic ( Ladurner et al, 2021 ); these different isoforms may provide nuanced targeting of cellular pathways. RORa has proven a target in LPS-associated septic shock in mice ( Hams et al, 2021 ), as well as surviving bacterial infection following severe burns injury, in rodents ( Ito et al, 2018 ). RORs are heavily intertwined with lipid metabolism and homeostasis ( Jetten et al, 2018 ), which has made them a focus for diabetes for example, although the immediate critical care implications are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The RORs have different tissue expressions; RORa is present predominantly in organs, while RORy is lymphatic ( Ladurner et al, 2021 ); these different isoforms may provide nuanced targeting of cellular pathways. RORa has proven a target in LPS-associated septic shock in mice ( Hams et al, 2021 ), as well as surviving bacterial infection following severe burns injury, in rodents ( Ito et al, 2018 ). RORs are heavily intertwined with lipid metabolism and homeostasis ( Jetten et al, 2018 ), which has made them a focus for diabetes for example, although the immediate critical care implications are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RORα gene expression is downregulated in the blood of 21 multiple sclerosis patients [63]. Recent studies suggested prominent role of RORα in regulating T cell and ILC2 development [64; 65] and immune cell functions, including T regulatory cells in allergic skin inflammation [66], Th17 driven inflammatory disorders [34; 67], survival of CD4+ T cells in colitis [68] and lung infection [69], ant-tumor immunity of liver-resident natural killer cells/ILC1s [70], macrophage activation in LPS-induced septic shock [71] and diet-induced obesity [72], and ILC3 driven fibrosis [73]. Both pro-inflammatory [74; 75] and antiinflammatory [76; 77] roles of RORα are observed in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Concerning the immune system, it has been reported that RORα is an essential factor for the activation of macrophages and the development of type 2 innate lymphocyte cells (ILC2) in the thymus. 25 , 26 In addition, RORα has been shown to play a role as an essential regulator of Th2 cell responses in allergic asthma and of the skin-resident Treg cells for repressing skin inflammation in atopic dermatitis. 27 , 28 In Th17 cells, which are significantly implicated in various inflammatory disorders, RORα has been reported as a transcription factor for Th17 differentiation and the expression of Th17-related genes, including its cytokines.…”
Section: Discussionmentioning
confidence: 99%